Subthreshold microsecond laser for proliferative diabetic retinopathy: a randomized pilot study - Jhingan M (Dove Medical Press, 2018)
Mahima Jhingan,1 Abhilash Goud,1 Hari Kumar Peguda,1 Mitali Khodani,1 Jeffrey K Luttrull,2 Jay Chhablani1 1L V Prasad Eye Institute, Kallam Anji Reddy Campus, Hyderabad, India; 2Ventura County Retina Vitreous Medical Group, CA, USA Aim: To compare the outcomes of subthreshold microsecond (STM) and continuous-wave laser (CWL) panretinal photocoagulation (PRP).Methods: In this randomized, prospective, pilot study, 20 eyes of 10 subjects with symmetric severe non-proliferative (NPDR) or low-risk proliferative diabetic retinopathy (PDR) were included. Each eye of the subject was randomized into either CWL or STM PRP group. Patients were evaluated at baseline and at months 3, 6, and 9 with color fundus photographs and visual field tests at each visit; however, electroretinography (ERG) was conducted at baseline and at month 9. The primary outcome measure was the difference in disease progression between the groups. Secondary outcome measures included change in visual acuity, contrast visual acuity, retinal sensitivity on visual field test, and change in ERG parameters.Results: During the 9-month follow-up, one eye of the STM group progressed to vitreous hemorrhage at the month 6 follow-up and required rescue conventional laser. The CWL group showed a drop in low-contrast visual acuity, visual field index, and scotopic b/a ratio in comparison to the STM group, although the difference was statistically insignificant (p>0.05).Conclusion: This prospective pilot study proposes microsecond PRP is non-inferior to CWL PRP and could be an alternative to CWL PRP to avoid associated complications in cases of severe NPDR and early PDR. Keywords: panretinal photocoagulation, diabetic retinopathy, proliferative diabetic retinopathy, micropulse laser, microsecond laser